A Qualitative Exploration of International Students’ Experience of Counselling Services at University - Najmi, Setareh (Université d'Ottawa / University of Ottawa, 2013)
This phenomenological qualitative study aimed to forefront international students’ experiences of receiving counselling services in a university setting. Three international students, recruited from two universities in eastern Canada using criterion sampling, were interviewed. Semi-structured interviews were audio-recorded and transcribed for analysis. In this phenomenological qualitative study, within- and between-person analyses were conducted for three transcribed interviews, from which eight main themes emerged: (a) openness towards seeking counselling, (b) hesitancy towards seeking counselling, (c) helpful aspects of counselling, (d) hindering aspects of counselling, (e) positive aspects of therapeutic relationship, (f) hindrances to therapeutic relationship, (g) counsellor’s cultural awareness, and (h) counsellor’s limited cultural awareness. The themes can be understood, and are explicated along four dimensions: seeking counselling, perceptions of counselling effectiveness, therapeutic relationship, and culture in counselling. The results from this study provide insight into international students’ counselling needs, expectations, and experiences. Special attention is given to the perceived expression of in-session counsellor cultural awareness and discussed using the integrated etic-emic framework. Implications for counsellors and university counselling services, limitations of the study, and recommendations for future research are provided.
Keywords: International Students; Counselling International Students; University Counselling Services; Integrated Etic-Emic Approach; Phenomenology; Qualitative